Objectivity of Morality (Value) - Petrus CKL Bello (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Ronald Dworkin refers to moral standards in law as legal principles. The inclusion of principles as inherent in law raises two problems. First, the problem of the objectivity of legal decisions: how to justify or account for a judge’s decision based on moral values? Is a decision based on moral values right or wrong? If the decision is based on morality, then it is possible that the decision taken will be biased by the judge’s own subjective judgment, then how to get objectivity? The issue of the objectivity of morality judgment occupies a central position in Dworkin’s legal theory. He believes that there is one correct answer for almost all legal issues without having to refer to elements outside of himself (non-legal elements). If moral judgment is "subjective" then the thesis about one correct answer cannot be defended. Second, Dworkin’s opinion that moral values are objective-which means that demands on these values are also objective-contains another problem, namely a moral dilemma resulting from a conflict between values. To answer this problem, Dworkin developed the notion of a unified value.